ANALISIS MAKNA KONOTATIF DAN SIMBOLIK DALAM PUISI „DIE ZWEI GESELLEN” KARYA JOSEPH VON EICHENDORFF - Giska Fanni Sihombing; Insenalia Roly Sampe Hutagalung; Tarida Alvina Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify 1) connotative meanings and 2) symbolic meanings in the poem Die zwei Gesellen by Joseph von Eichendorff and to analyze the application of Michael Riffaterre’s semiotic theory in revealing those meanings. The theory used in this research is Michael Riffaterre’s semiotic theory. The data in this research are the stanzas and lines in the poem Die zwei Gesellen by Joseph von Eichendorff, which consists of 6 stanzas and 5 lines in each stanza. The data were analyzed using descriptive qualitative techniques. The results of this study are as follows: connotative meanings are found in expressions that contain feelings, inner experiences, and indirect associations of meaning; symbolic meanings are found through symbols such as journey, nature, waves, and spring which represent the journey of human life. In addition, based on Riffaterre’s semiotic analysis, forms of indirect expression are found, namely displacing of meaning, distorting of meaning, and creating of meaning; and also matrix, model, and variants are found as the structure of meaning construction in the poem, as well as hypogram related to religious values and German Romantic tradition.